Synthesis and Characterization of UV-Initiated Anionic Polyacrylamide - Liao, Yong; Zheng, Huaili; Wei, Zhanchao; Tang, Xiaomin; Yang, Qingqing; Guo, Jinsong; Gao, Xu; Li, Fang; Chen, Wei (Asian Journal of Chemistry, 2014)
Assisted by ultraviolet initiation, an anionic polyacrylamide (APAM) was synthesized by acrylamide (AM), acrylic acid (AA) and sodium hydroxide. Through the single factor experiment, the optimum condition of preparing anionic polyacrylamide was investigated by using molecular weight as a indicator. Infrared radiation spectrum and scanning electron microscope were used to analyze the characterization of anionic polyacrylamide. The results show that anionic polyacrylamide with molecular weight of 16 million Da was prepared in the following optimum condition: MAM:MAA:MNaOH was 7.0:2.0:1.0, the total monomer concentration was 35 %, the initiator concentration was 0.15 %, the UV initiation time was 50 min, the urea concentration was 0.10 % and the EDTA concentration was 0.10 %. The active groups and net structure of anionic polyacrylamide were represented.